Analisis Penerapan Metode Mind Mapping Matkul Psikologi Komunikasi Islam di Institut Ummul Quro Al-Islami Bogor - Sofrada, Suci (Komunika: Journal of Communication Science and Islamic Dakwah, 2020)
A good learning process is the existence of activeness between educators and students and is supported by adequate learning methods and facilities. Islamic Communication Psychology (PKI) is a social subject (matkul) which has a lot of material that is written or reading material and is a new knowledge that they acquire in the world of education. The mind mapping learning method makes every student interact positively and actively. The position of educators in the mind mapping learning method is as a facilitator and consultant. Educators will only provide stimulation or inducement for discussion material. After that, students are free to develop their learning. In addition, educators also provide limits on the breadth of material for students. This study aims to analyze the process of delivering PKI subject matter material using the mind mapping method, whether it is able to make students more interested and easier to understand the material presented by the lecturers. Data collection through interviews with all students. This type of research is qualitative, in which all students become research subjects. The results of the research analysis show that the use of the mind mapping method increases student interest and creativity in attending lectures on the PKI subject. Abstrak Proses pembelajaran yang baik adalah adanya keaktifan antara pendidik dan peserta didik serta didukung dengan metode dan sarana prasana pembelajaran yang memadai. Psikologi Komunikasi Islam (PKI) merupakan bagian mata kuliah (matkul) sosial yang memiliki banyak bahasan materi yang bersifat tulisan atau bahan bacaan dan merupakan ilmu baru yang mereka peroleh.dalam dunia pendidikan. Metode pembelajaran mind mapping membuat setiap peserta didik berinteraksi secara positif dan aktif. Kedudukan pendidik dalam metode pembelajaran mind mapping adalah sebagai fasilitator dan konsultan. Pendidik hanya akan memberikan rangsangan atau pancingan materi pembahasan. Setelahnya peserta didik bebas mengembangkan pembelajarannya. Selain itu pendidik juga yang memberikan batas keluasan materi bagi peserta didik. Penelitian ini bertujuan menganalisa proses penyampaian materi matkul PKI dengan menggunakan metode mind mapping, apakah mampu membuat mahasiswa lebih tertarik dan mudah memahami materi yang disampaikan dosen pengampu. Pengumpulan data melalui wawancara kepada semua mahasiswa. Jenis penelitian ini adalah kualitatif, dimana semua peserta didik dijadikan subjek penelitian. Hasil analisis penelitian menunjukkan penggunaan metode mind mapping meningkatkan ketertarikan dan kreatifitas mahasiswa dalam mengikuti perkuliahan pada matkul PKI.